Determinação da taxa de infecção por Leishmania (Leishmania) chagasi utilizando técnicas sorológicas e diagnóstico molecular quantitativo em crianças residentes em área urbana de expansão da Leishmaniose Visceral - Leticia Helena dos Santos Marques (2010)
Nowadays, visceral leishmaniasis (VL) in Brazil has been regarded as a serious and emerging problem concerning Public Health for urban areas in major capitals. In that sense, asymptomatic infection diagnosis by Leishmania (Leishmania) chagasi in a given population can be considered as an indicator for outlining and assessing controlprogrammes. Nonetheless, epidemiologic inquiries based only on serology have shown limitations in asymptomatic diagnosis. In this study, tracing a profile which is more realistic about the situation of human VL in the Northwestern region of Belo Horizonte Minas Gerais, was looked for. In this context, infection rate by L. chagasi in 1875 children between 3 months and 7 years old was assessed by means of serologicinquiry as well as molecular examinations. After blood sample swab in filter paper, ELISA experiment with L. chagasi raw antigen (ELISA-AgT) and recombinant antigen rK39 (ELISA-rk39) was carried out. Positive resulting samples in at least one of those experiments (n=317) underwent molecular diagnosis by means of quantitative real timePCR (qPCR), using its gene SSU rRNA as a goal. Randomly, 242 negative samples were also selected for serologic classification so as to be assessed by qPCR. Considering positive samples in at least one of the serologic experiments, the infection rate was 16.9%. Regarding ELISA-AgT, infection rate was 2.8%, and according to ELISA-rk39, this same rate was 14.9%. Infection estimated prevalence based on qPCRwas 13.9%. When associating all these experiments, it can be verified a sensibility increase, and infection rate was up to 30.8%. It was possible to estimate parasitic burden in children diagnosed positively by qPCR. The average of parasitemia levels found between asymptomatic individuals was 56.5 parasites/blood mL (a normalised amount by extracted DNA nanogram). It was not observed any statistical difference for children sex and age variables when related to the results of diagnosis experiments. Results got showed the presence of asymptomatic infection by L. chagasi in the Northwestern region of Belo Horizonte. In addition, it is suggested that the association of more than one diagnosis technique can be considered as an alternative to carry outthe surveying of asymptomatic individuals in endemic area and that it also makes possible a better assessment and development of control measures which are more effective.